Crystal structure and Cu/Fe K-edge analysis of Ba0.5Sr0.5Fe1-xCuxO3-δ (x = 0–0.2) and the influence on conductivity. (July 2021) - Fitriana, F.; Baity, P.S.N.; Zainuri, M.; Kidkhunthod, P.; Suasmoro, S.
Abstract: Ba0.5 Sr0.5 Fe(1-x) Cux O3-δ (BSFC-x; x = 0–0.2) was synthesized and characterized. A sol-gel self-combustion method with mixed cation nitrate solutions and citric acid was used to synthesize BSFC-x precursors. Calcination was conducted in air at 850 °C for 6 h, followed by sintering in air at 1100 °C for 6 h. The phase, structure, and lattice parameters of the sintered BSFC-x were determined by X-ray diffraction (XRD). X-ray absorption near-edge spectroscopy (XANES) was used to analyze the oxidation state of the cation in the octahedron site (Cu/Fe). It showed that copper's oxidation state was predominantly 3+ due to oxygen octahedron neighbors in the crystalline symmetry and shifted to a lower oxidation state at 800 °C. The oxidation state was thought to be the predominant factor contributing to the overall conductivity through hole creation. The electrical analysis demonstrated semiconductor behavior at up to 500 °C that was influenced by the hole concentration, oxygen vacancies, and hopping distance. Above the maximum conductivity values, oxygen losses dominated the electrical response and disrupted the conductivity. Considering the doping quantity, the optimum doping was x = 0.1 with an electrical conductivity of ≈60 S/cm. Highlights: Cu doped BSFC-x structure transform from cubic for x ≤ 0.1 to tetragonal for x ≥ 0.15. The oxidation state of Cu predominantly 3+ at room temperature then reduce to 2+ for high temperature. The conduction dominated by thermally activated hole hopping through polaron B B − O − B B × . The concentration of holes depends on the oxidation state of Cu vis. oxygen vacancy.